VALIDASI DAN UJI LAPANGAN BAHAN PEMBELAJARAN GENERASI BARU (Studi pada Matakuliah Geografi dan Pelestarian Lingkungan dalam PIPS Universitas Terbuka) - Sri Sumiyati (JURNAL ILMIAH EDUNOMIKA, 2022)
This study aims to carry out the Validation and Trial of Learning Materials for the New Generation of Universitas Terbuka (UT) in Geography and Environmental Preservation in PIPS. This research was carried out in Conventional, Blended and Fully Online forms referring to steps 9 – 10 of the R & D model developed by Borg, Walter R. and Gall, Meredith D. (1983) for the macro scale, and the R & D model according to Borg and Gall (2007) for the micro scale. The results of the Preliminary Field Testing consist of input by 1) Content expert validation which includes material should not be used from the web, updated references, HOT question forms and updated material content; 2) Validation of Language Expert Instructional Design which includes more clarified drawing/illustration techniques, presentation of material plus instructions and sentences are good. The results of the Preliminary Product Revision by students (3 people) of UPBJJ-UT Jakarta, namely input in the form of being given instructions/material descriptions in the answer to the exercise. The Main Field Testing results consist of 1) UPBJJ-UT Purwokerto A total of 8 people, namely improvements to Modules 1-9 and each module a concept map is made; 2) UPBJJ-UT Semarang 4 people, namely the material is too broad and TTM Tutorial Guidance is needed; and UPBJJ-UT Jakarta 2 people, namely given instructions on the description of the material in the answers to the exercises.